(untitled) - Jorion, Philippe (Hoboken, N.J., 2009)
Financial Risk Manager Handbook, Fifth Edition supports candidates studying for the Global Association of Risk Professional's (GARP) annual FRM exam and prepares you to assess and control risk in today's rapidly changing financial world. Authored by renowned risk management expert Philippe Jorion-with the full support of GARP-this definitive guide summarizes the core body of knowledge for financial risk managers.
Keywords: Financial risk management,Risk management